Foreign Language Anxiety and Listening Comprehension of Monolingual and Bilingual EFL Learners - Mihaljević-Djigunović, Jelena; Legac, Vladimir (2008)
This paper discusses the results of a research study focusing on foreign language anxiety and listening comprehension in learning English as a foreign language (EFL). The study was carried out on a sample of 56 monolingual and 56 bilingual Croatian learners of EFL. The results point to significantly higher levels of language anxiety among monolingual than among bilingual learners in all three stages of the foreign language learning process, and significantly higher levels of listening comprehension of bilingual learners compared to mono-lingual learners. A significant negative relationship between language anxiety and achieve-ment in EFL listening comprehension was established in both of the studied groups.
Projekt MZOS
ENG